Systemic bank risk in Brazil: an assessment of correlated market, credit, sovereign and inter-bank risk in an environment with stochastic volatilities and correlations - Theodore M. Barnhill; Marcos Rietti Souto (Deutsche Bundesbank, 2008)
In this study we develop and demonstrate a powerful and flexible forward-looking portfolio simulation methodology for assessing the correlated impacts of market risk, and private sector, sovereign and inter-bank default risk on both individual banks (i.e. 28 of the largest Brazilian banks) and groups of banks (i.e. the Brazilian banking system). The methodology importantly accounts for bank asset and liability maturity and currency mismatches and loan portfolio credit quality and sector and region concentrations. In a significant innovation, financial and economic environment variables are modeled with stochastic volatilities and correlations. We demonstrate the reliability of the models by comparing simulated and historical credit transition probabilities, simulated and historical bank rates of return, and simulated versus actual bank credit ratings. When omitting sovereign risk our analysis indicates that none of the banks face significant default risk over a 1-year horizon. This low default risk stems primarily from the large amount of government securities held by Brazilian banks, but also reflects the banks' adequate capitalizations and extraordinarily high interest rate spreads. Once sovereign risk is considered and losses in the market value of government securities reaches 10 percent (or higher), several banks face potential solvency problems. These results demonstrate the well known risk of concentrated lending to a borrower which has a non-zero probability of default (e.g. Government of Brazil). We also demonstrate the potential systemic risk impact of variation in average recovery rates on defaulted private sector loans which reflect, among other factors, bank lending policies, the efficiency of the legal system in resolving defaults, and aggregate levels of defaults. Our analysis also highlights the importance of accounting for the differential risk characteristics of various banks and for the inter-bank risk channel, through which a systemic crisis may propagate. It further indicates that, in the event of a sovereign default, the Government of Brazil would face constrained debt management alternatives. To the best of our knowledge no one else has put forward a systematic methodology for assessing correlated market and credit (sovereign, corporate and inter-bank) default risk for a financial system. – – In dieser Studie wollen wir eine vorausschauende Methodik zur Einschätzung des systemischen Bankrisikos (der Wahrscheinlichkeit von multiplen Bankausfällen) entwickeln, die das Markt- und das Kreditrisiko anhand eines Portfoliosimulationsverfahrens integriert. Die Methodik soll sodann auf das brasilianische Bankensystem angewendet werden. Wir haben zahlreiche Simulationen durchgeführt, die sich auf umfassende Daten für 28 der größten brasilianischen Banken mit starkem Engagement im Bereich der staatlichen Kredite stützten. Im ersten Teil simulieren wir die Banken einzeln, wobei zwei Szenarien unterstellt werden: 1) die brasilianische Regierung ist immer in der Lage, ihre Inlandsschulden zu bedienen, und 2) die brasilianische Regierung kann zahlungsunfähig werden, wobei die Ausfallrate in etwa der durchschnittlichen Ausfallrate von Staatsschulden mit demselben Fitch-Rating wie Brasilien entspricht. Unsere Ergebnisse zeigen, dass einige Banken zwar tatsächlich Verluste verzeichnen, auch wenn eine Zahlungsunfähigkeit der Regierung nicht berücksichtigt wird, dass aber keine der Banken in dem einjährigen Simulationszeitraum einem nennenswerten Ausfallrisiko unterliegt. Wird allerdings der Ausfall der Regierung miteinbezogen, weisen mehrere simulierte Banken Probleme bezüglich des Ausfallrisikos auf. Zusammen betrachtet offenbaren diese Ergebnisse die negativen Seiten einer zu starken Kreditvergabe an den Staat. Erstens hindert ein zu hoher Bestand an Staatspapieren, selbst wenn die Regierung nicht zahlungsunfähig wird, die Banken daran, höhere (risikoreichere) Zinserträge aus Unternehmens- und Kundenkrediten zu erzielen. Zweitens ist es möglich, den der Regierung gewährten Kreditbetrag zu verringern und das Portfolio derart auszurichten, dass die Banken im Durchschnitt selbst dann noch gewinnbringendes Kapital erwirtschaften, wenn eine Zahlungsunfähigkeit der Regierung einbezogen wird. Wir weisen zudem nach, dass durchschnittliche und standardmäßige Abweichungen von der durchschnittlichen Gesamtkapitalrendite und der durchschnittlichen Eigenkapitalrendite für dieselben Momente unverzerrte Schätzwerte für die entsprechende historische Gesamtkapital- und Eigenkapitalrendite darstellen. Diese Erkenntnis ist aufgrund der Einschränkungen der Analyse zwar mit Vorsicht zu betrachten, doch zeigt sie, dass das Simulationsverfahren imstande ist, Ertragskennziffern der Banken nachzubilden, die hinlänglich mit den historischen Werten vergleichbar sind.
Keywords: G0; 330; Integrated Market and Credit Risk; Monte Carlo Simulation; Brazilian banks; Bankrisiko; Kreditrisiko; Bankensystem; Portfolio-Management; Simulation; Brasilien